Transformations in journalists' work and therapeutic management of professional pressure - Tavares, D.; Pegado, E.; Raposo, H. (Observatorio (OBS*), 2024)
In this article, we approach an unexplored line of analysis and research about the impact of transformations in journalists’ work on professional pressure and performance- consumption, what we refer to as the process of pharmaceuticalisation of work contexts. We discuss how changes at work lead to increased pressure on journalists and how pressure generates practices and dispositions for using different types of natural and pharmaceutical resources for managing work performance. Our analysis is based on mixed-methods research carried out in Portugal combining integrated qualitative and quantitative approaches. The results begin by highlighting the impact of work transformations on professional pressure both in terms of working time (workload, pace and working hours) and work demands resulting from professional practices and public scrutiny. The professional pressure that the transformations in journalism have been accentuating has faced journalists with the need to manage new or heavier work demands, which, in turn, can encourage the use of medicines and other therapeutic products to manage personal and professional performance.